1993
DOI: 10.2135/cropsci1993.0011183x003300020014x
|View full text |Cite
|
Sign up to set email alerts
|

Root Growth of Wheat Genotypes in Hydroponic Culture and in the Greenhouse under Different Soil Moisture Regimes

Abstract: Root characteristics of wheat (Triticum aestivum L.) genotypes are believed to be important in tolerance to drought and flooding, yet neither the extent of differences in root size among modern soft red wheat cultivars nor the degree of association between root size and drought or flooding tolerance is known. This study was conducted to see whether genotypes differ in root size, and to see if root size is associated with tolerance to flooded soil and to drought during early vegetative growth. We found differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0
1

Year Published

1994
1994
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 0 publications
3
20
0
1
Order By: Relevance
“…Cargill-163 showed the lowest RFW (2.05 g), while the other nine genetic materials presented higher root fresh weight, with no statistical differences among them. Drought drastically decresead RFW in winter wheat genotypes grown in greenhouse container culture for 3 weeks (MIAN et al, 1993). The trend demonstrated by Cargill-163 may be indicative of a sensitive genotype to drought stress.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Cargill-163 showed the lowest RFW (2.05 g), while the other nine genetic materials presented higher root fresh weight, with no statistical differences among them. Drought drastically decresead RFW in winter wheat genotypes grown in greenhouse container culture for 3 weeks (MIAN et al, 1993). The trend demonstrated by Cargill-163 may be indicative of a sensitive genotype to drought stress.…”
Section: Resultsmentioning
confidence: 87%
“…Over the years, physiological and morphological characteristics such as osmotic adjustment, stomatal behaviour, chloroplast activity, leaf water potential, root volume, root weight, leaf area, dry matter production, have been studied in several maize cultivars grown under limited water supply (MUSICK et al, 1965;SANCHEZ-DIAZ & KRAMER, 1971;NASS & ZUBER, 1971;MORGAN, 1984;WEERATHAWORN et al, 1992;MIAN et al 1993). It has been shown that maize has low drought tolerance due its high transpiration surface and poor root system (MALHERBE, 1964).…”
Section: Introductionmentioning
confidence: 99%
“…Resultados similares foram ralatados por Mian et al (1993), em que o crescimento radicular vigoroso resultou em crescimento vigoroso da parte aérea do trigo, por Girdthai et al (2010), em amendoim, e por Kennedy & Hutchinson (1999), em algodão. Isso leva a crer que a cultura tende a manter equilíbrio na sua relação raiz/parte aérea; a ocorrência de prejuízos em um dos fatores será acompanhada de redução do outro fator.…”
Section: Resultsunclassified
“…The development of root system can be promoted under moisture-defi cient conditions, even though it depends on the strength of the drought (Eghball and Maranville, 1993) and on both the species and the variety of plants Hida et al, 1995;Huang et al, 1997). A well-developed root system has also been reported in wheat plants grown under lower soil-moisture conditions (Proffi tt et al, 1985;Mian et al, 1993;Nakamura et al, 2003).…”
Section: Discussionmentioning
confidence: 99%